2004
DOI: 10.1159/000076124
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting Steps in the Development of Atherosclerosis: The Response-to-Influx Theory

Abstract: A large number of processes are involved in the pathogenesis of atherosclerosis but it is unclear which of them play a rate-limiting role. One way of resolving this problem is to investigate the highly non-uniform distribution of disease within the arterial system; critical steps in lesion development should be revealed by identifying arterial properties that differ between susceptible and protected sites. Although the localisation of atherosclerotic lesions has been investigated intensively over much of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…However, other investigators have argued that lipoprotein permeation becomes an increasingly important variable as lesions progress and may be a relevant factor in human atherosclerosis. 82,83 The uncertainty in this area allows us to only speculate about therapeutic opportunities. Previous work has suggested that blood pressure lowering, an important clinical intervention, reduced endothelial permeability to LDL.…”
Section: Lipoprotein Properties and Endothelial Permeabilitymentioning
confidence: 99%
“…However, other investigators have argued that lipoprotein permeation becomes an increasingly important variable as lesions progress and may be a relevant factor in human atherosclerosis. 82,83 The uncertainty in this area allows us to only speculate about therapeutic opportunities. Previous work has suggested that blood pressure lowering, an important clinical intervention, reduced endothelial permeability to LDL.…”
Section: Lipoprotein Properties and Endothelial Permeabilitymentioning
confidence: 99%
“…Staining was then examined in areas around arterial branch points; the strikingly nonuniform distribution of lipid deposition seen in such areas may reveal pathological mechanisms and has attracted considerable interest (reviewed by Weinberg 2004). The thoracic aorta from each animal was opened along its ventral wall so that the origins of four randomly-chosen intercostal arteries could be examined with each technique.…”
Section: Surgical and Lipid-staining Proceduresmentioning
confidence: 99%
“…The disease is characterised by a build up of lipid, inflammatory cells and fibrous proteins in the intima and inner media of the arterial wall. The precise mechanisms involved in the development of the disease, especially in its early stages, are still disputed, but the uptake of lipid-carrying plasma macromolecules is thought to play a key role (Nielsen, 1996, Weinberg, 2004, Tarbell, 2003, 2010; hence, studies of the rate of entry and transport within the wall of macromolecules could increase our understanding of the disease. Water transport, the subject of this paper, is important because much macromolecule transport is convective (A.…”
Section: Introductionmentioning
confidence: 99%